2014
DOI: 10.6018/analesps.30.3.152891
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Early Mathematical Competence, Gender and Social Background in Chilean Elementary School Population. [Relación entre los niveles de competencia matemática temprana, género y extracción social en la población escolar primaria en Chile]

Abstract: Título: Relación entre los niveles de competencia matemática temprana, género y extracción social en la población escolar primaria en Chile. Resumen: El artículo describe los niveles de competencia matemática temprana que presentan prescolares y estudiantes de primer ciclo de educación primaria chilenos, en los dominios de competencia relacional y numé-rica (N = 1437), evaluados mediante el Test de Evaluación Matemática Temprana versión Utrech (TEMT-U). El estudio permite constatar que existen diferencias sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
2
0
4
Order By: Relevance
“…Studies in Chile have also focused on variables associated with individual differences in the development of mathematical skills and academic performance in mathematics. Among these factors, and in line with the international literature, Chilean research has studied the attitudes and other motivational factors associated with learning mathematics (Cerda, Pérez, Aguilar, & Aragón, 2018;Cerda, Romera, Casas, Pérez, & Ortega-Ruiz, 2017), as well as sociodemographic and cultural variables that could affect it, such as the SES, family educational level and students' gender and age (Cerda, Pérez, & Ortega, 2014).…”
Section: Individual Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in Chile have also focused on variables associated with individual differences in the development of mathematical skills and academic performance in mathematics. Among these factors, and in line with the international literature, Chilean research has studied the attitudes and other motivational factors associated with learning mathematics (Cerda, Pérez, Aguilar, & Aragón, 2018;Cerda, Romera, Casas, Pérez, & Ortega-Ruiz, 2017), as well as sociodemographic and cultural variables that could affect it, such as the SES, family educational level and students' gender and age (Cerda, Pérez, & Ortega, 2014).…”
Section: Individual Differencesmentioning
confidence: 99%
“…Studies with children in early childhood education and the first years of primary school that studied individual differences with a focus on sociodemographic variables found dissimilar results. For example, Cerda et al (2014) found no differences by SES in the performance of early childhood-educated children and grade 1 and 2 children in the Utrecht Early Mathematical Competence Test. Nevertheless, del Río et al (2017) reported that children with low SES presented lower performance in solving applied mathematical problems, compared with those with high SES.…”
Section: Research On Numerical Cognition In Chilementioning
confidence: 99%
See 1 more Smart Citation
“…Una excepción es un estudio del año 2014, que se preguntó si, dada la brecha de género en rendimiento matemático en la adolescencia, las habilidades matemáticas eran ya distintas para niños y niñas en el primer ciclo de educación básica. Luego de aplicar pruebas que medían competencias numéricas, los resultados no mostraron diferencias entre niños y niñas de seis y siete años de edad (Cerda, Pérez & Ortega-Ruiz, 2014). Otro estudio nacional relevante es uno comisionado en 2008 por el Servicio Nacional de la Mujer (Sernam), dirigido a examinar las interacciones, desde una perspectiva de género, entre los profesores y estudiantes en escuelas públicas.…”
Section: Estereotipos Infantiles Acerca Del Género Y El Desempeño Acaunclassified
“…Tercero, que, en Latinoamérica, el tema de la brecha de género, si bien ha sido estudiado, se ha abordado más a partir de constructos como los estereotipos y las actitudes hacia las matemáticas presentes en el aula de clase y en la familia en diferentes niveles escolares (Cerda, Pérez & Ortega-Ruiz, 2014;Espinoza & Taut, 2016;González-Pineda et al, 2006;Del Río, Strasser & Suspurreguy, 2016;Mizala, Martínez & Martínez, 2015;Valle, Reguerio, Piñeiro, Sánchez, Freire & Ferradás, 2016), pero no desde la amenaza de estereotipo.…”
Section: Introductionunclassified